PENGARUH KOMPRES HANGAT PADA PAYUDARA TERHADAP KELANCARAN ASI PADA IBU POST PARTUM DI KLINIK LALA MEDICARE DEPOK TAHUN 2023 - Febriana, Tyas (Journal of Midwifery Tiara Bunda, 2023)
Background: Breast milk is a complex food because it contains complete nutrients, which are ideal nutrients to support optimal health, growth and development of infants. Excellent breast milk production is known from the sufficient needs of breastfeeding needs to the baby supported by several factors such as peace of mind and soul, breast care, rest patterns and child suckingWarm compresses of the breast during breastfeeding will be able to increase the flow of milk from the milk- producing glands. Purpose of the study: to determine the effect of warm compresses on the smoothness of breast milk in postpartum mothers at the lala medicare clinic in 2023. Research method: is quantitative research. The research design used Quasi Experiment, namely pre test - post test design with a sample size of 15 respondents. The population in this study were all mothers who breastfeed at the Lala Medicare Clinic in Depok. The sample in this study was determined by Accidental Sampling technique so that a total of 15 respondents were obtained. Statistical test used is Wilcoxon test. The results showed: that there was a difference in breast milk fluency after the intervention with a P-value of 0.003, the result was <0.05. The results of this study are expected to be used as an alternative therapy for breastfeeding mothers who experience problems with breast milk fluency. Conclusion: there is an influence between warm compresses with smooth breast milk in post partum mothers